The Potential for the Development of Critical Thinking Tests : An Overview of Educators’ Perceptions - Hidayati, Nurkhairo; Suryanti, Suryanti; Cahaya, Nilam (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aimed to investigate teachers’ perceptions about the need to develop critical thinking tests. The research method used quantitative descriptive. Research involved 20 biology teachers who taught at the senior high school in Riau. The data collection instrument was a questionnaire accompanied by a discussion with the teacher. The questionnaire contained questions regarding the teacher’s knowledge of critical thinking, the availability of critical thinking instruments, and their implementation in learning. Data analysis was carried out in a quantitative descriptive. The results of the study show that the teachersâ€™ knowledge of critical thinking is developing. The teacher also explained that it is crucial for students to have critical thinking skills so that measurements need to be taken. The availability of instruments to measure critical thinking when viewed from the percentage of teachers who provide them is 70%. In its implementation, the teacher makes critical thinking questions sourced from the question bank, articles, and books. The questions prepared by the teacher are also able to measure critical thinking even though they do not yet cover all aspects of critical thinking. Based on the research results, it can be recommended that the development of critical thinking tests can be carried out by the aspects of critical thinking (basic clarification, bases for a decision, inference, advanced clarification, supposition and integration, and strategies and tactics) and in line with the material being studied at school.